Pembelajaran Daring Pada Mata Pelajaran Matematika Selama Pandemi Covid-19 di SMA Negeri 9 Mataram - Arthina Utami; Sripatmi Sripatmi; Syahrul Azmi; Sri Subarinah (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine the order of the use of online learning platforms, the opinion of mathematical subjects teachers on the implementation of online learning, the obstacles encountered by mathematical subject teachers in using online learning platforms and the mathematics learning outcomes of students during online learning. The research method used is a mixed method. The subjects in this study were mathematics subject teachers, principal, vice principal in the curriculum field and students in class XI MIA 2 and XI MIA 4. The data collection techniques used were questionnaires, interviews and tests. The results showed that the easiest online learning platform to use to teach mathematics, monitor student activities and the most wasteful use of internet quota was the Zoom platform. The online learning platform that is easiest to use for evaluating mathematics subjects and the easiest to use for checking student learning outcomes is the Google Classroom platform. Mathematics subject teachers disagreed with the implementation of online learning. The obstacles encountered were difficulties in preparing, controlling and supervising students, making attractive learning models and media, using online learning platforms, teaching some materials, distinguishing students who took cooperation or independent work exams and learning facilities. students and internet networks. Meanwhile, the mathematics learning outcomes of students during online learning were not yet complete.